Patients, clinicians and open notes: information blocking as a case of epistemic injustice - Blease, Charlotte (Journal of medical ethics, 2022)
In many countries, including patients are legally entitled to request copies of their clinical notes. However, this process remains time-consuming and burdensome, and it remains unclear how much of the medical record must be made available. Online access to notes offers a way to overcome these challenges and in around 10 countries worldwide, via secure web-based portals, many patients are now able to read at least some of the narrative reports written by clinicians (‘open notes’). However, even in countries that have implemented the practice many clinicians have resisted the idea remaining doubtful of the value of opening notes, and anticipating patients will be confused or anxious by what they read. Against this scepticism, a growing body of qualitative and quantitative research reveals that patients derive multiple benefits from reading their notes. We address the contrasting perceptions of this practice innovation, and claim that the divergent views of patients and clinicians can be explained as a case of epistemic injustice. Using a range of evidence, we argue that patients are vulnerable to (oftentimes, non-intentional) epistemic injustice. Nonetheless, we conclude that the marginalisation of patients’ access to their health information exemplifies a form of epistemic exclusion, one with practical and ethical consequences including for patient safety.